Mejoramiento de las aguas residuales tratadas en las lagunas de estabilizacion de San José de Chiclayo – Lambayeque – mediante humedales - Renteria Campos, Enrique Gaston (2020)
ABSTRACT The wastewater treatment system in Chiclayo was put into operation with 10 stabilization lagoons inaugurated on December 2, 1998. 5 are anaerobic lagoons and 5 are optional lagoons. An average of 200 thousand new users were benefited with the integral sewerage system. Likewise, 1400 hectares of the peasant community of San José are irrigated for long-stemmed vegetables, which is a valuable contribution to agriculture. However, an effluent channel from the last optional lagoon leads directly to the sea as a receiving body. In the present research work in order to reduce pollution parameters, an artificial wetland with water hyacinth (Eichhornia crassipes) was built, at the laboratory level so that a free surface wetland type lagoon is constructed to minimize or eliminate the contaminants present in the effluent of the last lagoon (F5), removal percentages of 7.62 for conductivity, 100 for BOD5, 50 for total suspended solids, 97.2 for total coliforms and 99.96% for coliforms were obtained thermo tolerant. Likewise 68% for chromium VI, 55.1 for lead and 33.33 for cadmium. Finally, comparing with the permissible limits of total coliforms was 1.5 E + 04, thermo-tolerant coliforms was 2.1E + 02 which compared to the permissible limits of the WHO and ECA-water it is possible to use for irrigation of tall and low stemmed vegetables .